Immunogenicity of a prophylactic quadrivalent human papillomavirus L1 virus‐like particle vaccine in male and female adolescent transplant recipients. (1st February 2014) - Gomez‐Lobo, V.; Whyte, T.; Kaufman, S.; Torres, C.; Moudgil, A.
Abstract Organ TX recipients are at an increased risk of developing cancers of the lower genital tract related to HPV. The quadrivalent HPV vaccine has high efficacy in preventing these diseases, but response to many vaccines is suboptimal after organ transplantation. Liver and kidney TX recipients received quadrivalent HPV vaccine. Serum samples were tested for anti‐HPV levels. Of 20 renal transplant recipients screened, 14 received vaccine. Of these, seven completed the vaccine series and seven had incomplete vaccination. Of five liver TX children, three received vaccines (two complete and one incomplete). All eight kidney and liver TX children with complete vaccination and available results were seronegative at baseline and had seroconversion at month 7 for all four HPV types. Six of 14 (42.8%) kidney TX recipients developed AR. During the same time period, eight of 28 (28.5%) non‐vaccine renal transplant recipients developed AR (p = ns). Transplant adolescents developed 100% seroconversion to all four HPV serotypes with HPV vaccine with serologic titers similar to historic controls. A non‐significant increased incidence of AR was noted among kidney transplant vaccine recipients. A much larger study would be needed to evaluate whether HPV vaccination increases AR in transplant adolescents.